Progress in Botany Vol. 79 (Progress in Botany,, 2018)
With one volume each year, this series keeps scientists and advanced students informed of the latest developments and results in all areas of the plant sciences. The present volume includes reviews on plant physiology, biochemistry, genetics, ecology, and ecosystems.